BIAYA TAHUNAN PATEN CIVITAS AKADEMIKA UNIVERSITAS TRISAKTI YANG TIDAK TERKOMERSIALISASI: Annual Fee For Non-Commercial Patents Of Trisakti University Academicians - Marsha Prastari; Aline Gratika (AMICUS CURIAE, 2025)
When a patent application has been granted and the patent has been registered in the general register of patents, the patent begins to receive protection. Thus, the owner or holder of the patent has the right to exercise the patent rights himself. In addition to these rights, as a result of patent protection, the patent owner/holder has several obligations, one of which is to pay the annual patent fee, to any patent owner/holder including universities, is Trisakti. The indentification problem in this research is about the payment of annual fees for patents that are not commercialized, in this case patents at Trisakti. The result and the conclusion shows that based on Article 21 of Law No.13 Year 2016 of Patent, there is no exception in the payment of annual fee. The reason for not commercializing a patent cannot be the reason for not paying the annual fee. Therefore, Trisakti as the holder of patent rights from its academic community is still obliged to pay annual fees. No Trisakti patent has been successfully commercialized, but Trisakti still pays the annual fee because if the annual fee is not paid, the consequence is that the patent rights will be revoked.